Regeneração óssea de cavidades cirurgicamente criadas e preenchidas com osso autógeno ou osso heterógeno: análise histomorfométrica em calotas de ratos - Guskuma, Fabiano Uehara [UNESP] (2010)
The purpose of this study was to evaluate the bone regeneration of defects surgically created and filled with autogenous bone crushed graft or bone heterogeneous implant (Bio Oss ® 0.5 g Granules 1cc 0.25 to 1 mm). Were used 32 rats. In each animal were performed, with trephine's aid, two bone's defects of 5 mm of diameter in calvaria. The animals in the Control Group had defects filled only with the clot itself; in the Heterogeneous Implant Group (IH), the defect was filled with heterogeneous crushed bone, and in the Autogeneous Crushed Bone Group (OAT) it was filled with autogenous crushed bone. The animals were sacrificed at the periods of 7 and 30 days postoperatively. By the 7th day, in all the 3 groups, was observed the formation of conjunctive tissue, and in both, control groups and OAT, a small bone formation at the edges of the defect. In the 30th day was observed, in the control group, a new bone formation originated from the edges of the bone remaining and the rest of the defect remained filled with conjunctive tissue. There was a new bone formation around the particles of the graft and at the edges of the defect in the OAT Group. And, in IH Group was observed the permanence of the implant and a slight new bone formation. The methodology allows us to conclude that Bio-Oss® has biological properties and osteoconductive less important than those of Autogenous Bone